Knocking Out of CEACAM1 Can Reduce Oxidative Stress and Promote Cell Proliferation in the HPMVECs under Hypoxia - Zhixuan Li; Xiaokang He; Xueting Zhang; Junhua Zou; Hao Li; Jing Wang (Journal of Immunology Research)
Pulmonary hypertension (PH) induced by hypoxia is common in clinical practice and often suggests a poor prognosis. The oxidative stress and proliferation of pulmonary vascular endothelial cells caused by hypoxia are the major mechanisms involved in the pathophysiology of PH. It has been reported in recent years that the carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) promotes angiogenesis. In this study, normal human pulmonary microvascular endothelial cells (HPMVECs) and HPMVECs with stable knockout of CEACAM1 by CRISPR-Cas9 were subjected to oxygen-glucose deprivation/reperfusion (OGD/R) to induce hypoxic conditions. JC-1, ROS, and cell cycle profile were analyzed for each cell line and controls, using flow cytometry. A tube formation assay was used to detect angiogenesis, along with expression levels of CEACAM1, TNF-α, VEGF, VEGFR-2, p-P38/P38, and CyclinD1 proteins (to distinguish profiles of angiogenic growth and cell proliferation). We observed increased expression of CEACAM1 in HPMVECs after OGD/R, while ROS production was reduced and mitochondrial membrane potential was increased after OGD/R in CEACAM1-/- HPMVECs. Furthermore, we observed increased cell division in CEACAM-/- HPMVECs, accompanied by enhanced angiogenesis and reduced TNF-α protein expression and increased VEGF, VEGFR-2, and CyclinD1 expression. Together, these data suggest that upregulation of CEACAM1 in HPMVECs under hypoxic conditions may damage cells by increasing oxidative stress and inhibiting cell proliferation.